Wealth index and risk of childhood overweight and obesity: evidence from four prospective cohorts in Peru and Vietnam. - Carrillo Larco, Rodrigo M. (2015)
OBJECTIVES: To estimate the incidence and risk of childhood overweight and obesity according to socioeconomic status in Peruvian and Vietnamese school-aged children. METHODS: Longitudinal data from the Young Lives study were analyzed. Exposure was wealth index in tertiles. Outcome was overweight and obesity. Cumulative incidence per 100 children-years, relative risks (RR), and 95 % confidence intervals (95 % CI) were calculated. A hierarchical approach, including child- and family-related variables, was followed to construct multivariable models. RESULTS: The cumulative incidence of overweight and obesity was 4.8 (95 % CI 4.1-5.5) and 1.7 (95 % CI 1.3-2.2) in the younger and older Peruvian cohort, respectively; and in Vietnam 1.5 (95 % CI 1.2-1.8) and 0.3 (95 % CI 0.2-0.5), respectively. The incidence of overweight and obesity was higher at the top wealth index tertile in all samples. In the older cohorts, comparing highest versus bottom wealth index tertile, RR of overweight and obesity was four to nine times higher: 4.25 in Peru (95 % CI 2.21-8.18) and 9.11 in Vietnam (95 % CI 1.07-77.42). CONCLUSIONS: The results provide important information for childhood obesity prevention in countries moving ahead with economic, epidemiological and nutritional transitions.